Self-Confidence and Peak Performance: A Descriptive Study on Young Basketball Athletes - Mayangsari, Salamah; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Jorpres (Jurnal Olahraga Prestasi), 2024)
Cases in the field reveal that there are always results matches that are not as expected due to the non-achievement of peak performance. Various factors influence it, specifically, the author highlights self-confidence which is a major psychological aspect that effectively contributes to an athlete's peak performance. effectively contributes to an athlete's peak performance, where a high level of high level of self-confidence can make the athlete able to do a better job. their work better. Quantitative descriptive research with correlational design and using purposive sampling technique in determining the sample. Research sample of 30 youth basketball athletes (19 male and 11 female). Instrument research instrument in the form of two questionnaires given to athletes to measure confidence and peak performance given once to the sample via google forms. Data analysis was carried out using Statistical Program for Social Sciences (SPSS) version 25 using pearson correlation. The results showed a significant relationship between self-confidence and peak performance of youth basketball athletes. So it can be concluded that it is important for athletes to have the right self-confidence during the stages of training and competition because it contributes to the peak performance of youth basketball athletes.